Solutions to Exercises in Intermediate Statistical Methods - Wetherill, G. Barrie. author. aut Link
VI, 74 p.
Keywords: This booklet contains hints to the solutions and answers where necessary, of the exercises contained in 'Intermediate Statistical Methods' by G. Barrie Wetherill. The following principles have been adopted in dealing with the answers. (1) In some cases the answer is the drawing of a graph, and this has been omitted. (2) In many numerical exercises a considerable amount of 'data snooping', plotting of residuals, etc. should follow the main ~sis. The inclusion of this material would make the answer booklet far too long. (3) In some cases there is a readily available reference from which the answer can be ob~ained, in which case reference has been made to this. It is not necessary to work through every exercise , but it should be recognised that the exercises are an integral part of the main text, and a comprehensive grasp of the subj ect cannot be obtained without attempting a substantial proportion of them. It is hoped that this booklet will be of assistance in pointing the way, and providing a check on the more vital calculations. The importance of numerical exercises should be stressed, and it is here that Appendix B is of importance. There is abundant material available there in many different fields of application. Currently we are in the process of mounting a form of Appendix B on a computer, together with accessing programs.